EVALUASI EFEKTIVITAS PROSES REKRUTMEN DAN SELEKSI KARYAWAN DALAM MENINGKATKAN KINERJA PERUSAHAAN - Putri Indriyana Silvia; Solehudin Solehudin; Nunung Nurhasanah (Universitas Bina Taruna Gorontalo, 2024)
This study aims to evaluate the effectiveness of the recruitment and employee selection process in improving company performance, with PT Haramai Jaya Nusantara as a case study. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and document analysis. The results of the study show that the recruitment and selection process at PT Haramai Jaya Nusantara has not been fully effective in improving the company's performance. This is due to several factors, such as: Selection criteria that are not clear and measurable; Inadequate selection methods; Lack of training for interviewers; and an onboarding process that is not optimal. This study recommends several steps to improve the effectiveness of the recruitment and selection process of employees at PT Haramai Jaya Nusantara, including: Defining clear and measurable selection criteria; Using more appropriate selection methods, such as ability tests and personality tests; Providing training for interviewers; and improve the onboarding process to help new hires adapt to the company. It is hoped that by implementing these recommendations, PT Haramai Jaya Nusantara can increase the effectiveness of the recruitment and selection process of employees in the future so that it can produce qualified and outstanding employees to be able to improve the company's performance.